The Decrease of Pulmonary Artery Acceleration Time is Associated with Delayed Heart Rate Recovery in Hypertensive Male Subjects Without Diabetes Mellitus. (June 2015) - Winata, Johan; Rotty, Monique; Azis, Razak Abd.; Panda, A. Lucia
Abstract : Background: Delayed heart rate recovery (HRR), commonly found in diabetes and hypertensive patients, has been associated with increasing morbidity and mortality in patients with pulmonary arterial hypertension (PAH) instead of the causes. Objectives: This study is aimed to determine the correlation between pulmonary artery acceleration time (PAT), as determinant of PAH, and delayed HRR in hypertensive patients. Methods: This is a cross sectional observational study. Fourty consecutive male hypertensive patients without diabetes, chest pain, and known CAD were included. They underwent trans-thoracic echocardiography (TTE) and treadmill stress testing (TST). HRR was measured using TST at first-, second-, and third-minute after exercise. Pulmonary artery acceleration time (PAT) was measured using TTE. The correlation between PAT and HRR was analysed using linear logistic regression test. Results: PAT was significantly correlated with HRR at first-(R = 0.325, p = 0.041), second- (R = 0.362, p = 0.022), and third-minute (R = 0.353, p = 0.026) after exercise. Conclusion: The decrease of PAT is significantly associated with delayed HRR at first-, second-, and third-minute after exercise.